The impact of sport hypnosis on volleyball athlete performance: An empirical study - Hasyim, Andi Hasriadi; Amirzan; Muhammad; Humaedi; Sujarwo (Journal Sport Area, 2023)
In athlete coaching, mental factors often receive less attention than physical factors, such as technique, tactics, and strategy. This study explored the use of hypnosis as a mental exercise in coaching volleyball athletes. This study was conducted on 20 PBVSI volleyball athletes in Pidie Regency using an experimental one-group pretest-posttest design and then tested their abilities using the American Association for Health, Physical Education, Recreation, and Dance (AAHPERD) volleyball playing skills test. The collected data were analysed using inferential statistics (specifically the t-test) with SPSS 27 at the 0.05 level of significance. The results showed a significant improvement in volleyball playing skills after hypnosis training, indicating its potential application in athlete coaching. Hypnosis was found to significantly improve concentration, confidence, and emotional control among athletes—key elements that contributed to overall sports performance. However, limitations of this study include the small sample size and focus on one type of sport. Therefore, further research involving larger samples across different sports is recommended for wider generalisability. In addition, long-term studies are needed to assess the sustained effects of hypnosis over time. In conclusion, our preliminary findings underscore the potential benefits of integrating mental training techniques such as hypnosis into athletic training programmes to improve performance outcomes. These results highlight the importance of considering psychological aspects alongside physical aspects in athletic training.